Reply to comments contained in "are the reactions of quinones on graphite adiabatic?", by N.B. Luque, W. Schmickler [Electrochim. Acta xx (2012) yyy] - Batchelor-Mcauley, C; Laborda, E; Henstridge, M; Nissim, R; Compton, R (2013)
This response article aims to provide an overview of the literature highlighting experimental work that, in contrast to the account by Luque and Schmickler, evidences the non-adiabatic nature of the electron transfer process. © 2012 Elsevier Ltd. All rights reserved.